PENGETAHUAN DAN PENERAPAN GERMAS PIS-PK PADA KELUARGA BINAAN KESEHATAN FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA TAHUN 2020 - HANNY RAHMI LUBIS; DES SURYANI (LP2MTBM MAKARIOZ, 2021)
In an effort to improve the quality of health in Indonesia, the president initiated a national movement, namely GERMAS. Theimplementation of GERMAS activities starts from the family level as the smallest part of the community. In order to supportthis government movement, the UMSU Faculty of Medicine also created a program called the health assisted familyprogram. The program, which has been running since 2013, aims students to educate the target family to live healthier life.However, so far there has been no analysis of the results of this activity, both regarding the knowledge and also the dailyapplication of GERMAS PIS-PK by the assisted families. Therefore, the researcher wants to assess the knowledge andapplication of the family and see the relationship between them. To determine the relationship between the knowledge of thetarget family community on GERMAS PIS-PK and their application to the program. Observational research with crosssectional design in the health assisted families of FK UMSU class of students 2017. Research data were obtained fromprimary data using a knowledge questionnaire about GERMAS PIS-PK and a questionnaire on the application of GERMASPIS-PK. Then do the analysis with the Fisher test. There were 28 families (96.6%) with good knowledge and there were 28families (96.6%) who had applied GERMAS PIS-PK. The results of the Fisher test showed that there was a significantrelationship between the knowledge of the assisted families about GERMAS PIS-PK and the application of GERMAS PIS-PKwith a value of P = 0.034 (p <0.05). The families who have good knowledge about GERMAS PIS-PK also apply GERMASPIS-PK well in their daily life.